Checking the Consistency of Combined Qualitative Constraint Networks - Cohen-Solal, Quentin; Bouzid, Maroua; Niveau, Alexandre (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
We study the problem of consistency checking for constraint networks over combined qualitative formalisms. We propose a framework which encompasses loose integrations and a form of spatio-temporal reasoning. In particular, we identify sufficient conditions ensuring the polynomiality of consistency checking, and we use them to find tractable subclasses.